Psychiatrization as a mechanism for handicapping students with intellectual disability. Psychiatrisation in education - Beata Gumienny (Edukacyjna Analiza Transakcyjna)
Psychiatryzacja jako mechanizm upośledzania uczniów z niepełnosprawnością intelektualną. Psychiatryzacja w edukacji